Nurses' Perception Of The Implementation Of Computer-Based Nursing Information Systems In Hospitals - Yenny Sima; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Advances in information technology have significantly transformed healthcare services , including nursing Computer -Based Practice Nursing Information Systems (CBNIS) are innovations designed to improve documentation efficiency , communication , and patient data management . Nurses ' perceptions of these systems play an important role in determining successful implementation . This study aimed to identify nurses ' perceptions regarding the implementation of Computer-Based Nursing Information Systems in hospitals . This study employed a quantitative approach with a cross-sectional analytical design . The sample consisted of 50 nurses working in inpatient wards and selected through purposive sampling. Data were collected using nurse perception questionnaires and observation sheets regarding system utilization . Data were analyzed using univariate and bivariate analyses with the Chi- Square test . The results showed that 70% of respondents had positive perceptions of the implementation of computer-based nursing information systems . Most nurses reported that the system improved documentation efficiency , facilitated access to patient information , and enhanced the quality of nursing care . Statistical analysis revealed a p- value of 0.001 (p < 0.05), indicating a significant relationship between nurses ' perceptions and the effectiveness of system implementation . Keywords : Nursing Information Systems, Information Technology, Nurse Perception , Nursing Documentation , Hospital